Temporal Markers as a Way of Modeling the Artistic Space of the Poem “Pe aceeași ulicioară” by M. Eminescu - A. V. Diehl (Дискурс)
Introduction. The present study is devoted to the analysis of linguistic and cultural specifics and features of the functioning of temporal markers that model the artistic space of the poem “Pe aceeași ulicioară” by M. Eminescu. The universal category of temporality becomes the object of research at the intersection of various scientific disciplines: linguistics, psycholinguistics, literary criticism and cultural studies. Thus, the relevance of this study is primarily due to its interdisciplinarity. The novelty of the study lies in the fact that the linguocultural analysis of temporal markers in the poem “Pe aceeași ulicioară” by M. Eminescu is carried out within the framework of the anthropocentric paradigm. The purpose of the study is to identify the specifics of the temporal structure of the poem “Pe aceeași ulicioară”, taking into account the meaning-forming function of temporal markers in its cognitive scenario, structuring the temporal perspective of the poem and modeling the emotional world of the lyrical hero.Methodology and sources. The theoretical basis of the study is presented by the works of linguists who analyzed the essence of the category of temporality, as well as the linguocultural specifics of emotional concepts in the anthropocentric paradigm. In this article, when analyzing the language material, the following methods were used: the method of conceptual-frame analysis, the descriptive method, the contextual and interpretive methods.Results and discussion. In the center of the artistic space of the literary works of M. Eminescu is his lyrical hero with his rich inner world an emotional person, nostalgic for the past and sensitively responding to the change of mood in his contemporary society. The article presents the results of the categorization of temporality markers, the lexemes that structure the time plans of the present and the past in the context of describing the emotional world of the lyrical hero.Conclusions. It has been found out that the temporal markers in the poem “Pe aceeași ulicioară” by M. Eminescu perform the function of localizing the events described in the poem within the artistic space of the poem, correlating them with the temporal plan of the present or past, and thus structure the world of emotional experiences of the lyrical hero. The artistic concepts “past”, “present” and “love” considered in the article closely interact and echo each other. The semantic dominant of the poem is the concept of love, which unites the selected concepts within the storyline of the poem, which is partly autobiographical.